The relative roles of early life, physical activity, sedentarism and diet in social and economic inequalities in body mass index and obesity risk between 9 and 18 - Richard Layte; Frances M. Cronin; Sanna Nivakoski; Olivia McEvoy; Ross Brannigan; Debbi Stanistreet (Elsevier, 2023)
Background: Studies in many middle and high-income countries describe an increasing prevalence of adiposity and obesity among children and adolescents. Prevalence is higher among families of low socioeconomic position (SEP) and systematic reviews have identified relevant factors, but have not quantified their relative importance to SEP differentials. This paper examines the relative importance of different factors to Body Mass Index (BMI) and obesity trajectories from age 9 to age 17/18. Methods: Multi-level models of child BMI/obesity risk trajectory by maternal education were conducted using a nationally representative cohort of children born in Ireland in 1998 and aged 9 at baseline (N = 8568), with follow-up at 13 and 17/18 years (88% and 73% response rate respectively). Models were stratified by sex and both time-varying (e.g. child physical activity, diet, sedentary activity) and time-invariant (e.g. early life) factors were tested. Results: Significant inverse gradients in BMI and obesity risk by level of maternal education were present across both sexes and at each age; unadjusted absolute differentials in obesity risk between highest/lowest education groups increased by 56% for males and 42% for females between age 9 and 17/18. Early life factors accounted for 22% of the differential in obesity risk between the lowest and highest education groups among males at age 9, falling to 13% at 17/18. Among females the proportion fell from 33 to 23%. Unadjusted absolute high/low maternal education group differentials in BMI were 7.5 times higher among males and 11 times higher among females at 17/18 than at age 9. Conclusions: Given the importance of early life exposures to subsequent differentials in BMI and obesity risk our findings suggest that policy makers should focus resources on primary prevention during the prenatal and early life period if they wish to reduce the prevalence of child and adolescent obesity.